2018
DOI: 10.1111/bjet.12604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of student agency on learning performance and learning experience in a flipped classroom

Abstract: The efficacy of the flipped classroom model largely depends on the specifications of its design and implementation, and one important specification to consider is student agency. With the purpose of prescribing the optimal level of student agency for the flipped classroom, this study conducted a repeated‐measures experimental design to compare the effects of three levels of student agency in an undergraduate flipped course with 43 students. The empirical results revealed that student agency had a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 39 publications
3
52
0
7
Order By: Relevance
“…The technology‐enhanced FC was effective, engaging and facilitated active learning better than the conventional instructional setting, which is consistent with previous findings (Blair et al ., ; Chuang et al ., ; Luo et al ., ). Students were highly satisfied with their training and maintained a positive attitude during their training sessions (Costley & Lange, ; Long et al ., ; Thai et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The technology‐enhanced FC was effective, engaging and facilitated active learning better than the conventional instructional setting, which is consistent with previous findings (Blair et al ., ; Chuang et al ., ; Luo et al ., ). Students were highly satisfied with their training and maintained a positive attitude during their training sessions (Costley & Lange, ; Long et al ., ; Thai et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Although many studies demonstrated students’ preference for FCs, positive attitudes alone may not be sufficiently compelling evidence for educators to convert to a FC approach (Chen et al ., ). Due to lack of conclusive findings, further empirical evidence about the effect of FC on academic performance and student satisfaction is needed (Chuang et al ., ; Luo et al ., ; O’Flaherty & Phillips, ). This study investigates whether a FC can impact learning effectiveness for instructional media design courses, leading to better academic performance and training satisfaction by comparing a flipped and a traditional class.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations